Austrian citizenship for South Tyrol: Another Hungarian-Slovak tit-for-tat? - Gattringer, Robert (Riga Graduate School of Law, 2018)
The subject of this thesis is the question, whether Austria can provide South Tyrol or, more specifically, individual South Tyroleans with the Austrian citizenship under the terms of public International Law. The relevance of this topical question is given for a number of reasons. Today the European Union has to face massive problems, to name but a few: economic protectionism of the closest ally (USA), frozen conflict in a neighbour state (Ukraine crisis, annexation of Crimea by Russia), Russia is deploying nuclear-capable missiles in Kaliningrad2, but moreover challenges from within: member states are changing their system of government in a way it can be feared they are leaving shared European values behind (Hungary, Poland), right wing populist parties are largely gaining the voters’ approval (Austria, Germany, Hungary, Italy, Poland) and regions of European member states are interested in leaving their host countries and becoming independent (Catalonia, Scotland).
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Public international law; Citizenship, Austria